Kajian Arsitektur Simbolik pada Museum Fatahillah - Warda, Ankalona Syurya; Galax Putra Jagat Paryoko, Vijar (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Its unique character makes Fatahillah Museum holds many things that are symbolic. However, the lack of understanding and observation of the surroundings makes the symbolic elements as architectural elements of Fatahillah Museum look weakened. The study of symbolic architecture in Fatahillah Museum is expected to contribute to public understanding of the history of Jakarta and the meanings contained in the building. The symbols and hidden meanings that the designer wants to convey can be revealed to the wider community. Therefore, this research aims to help researchers to find out how the application of symbolic in architecture. In this research, the author uses a descriptive qualitative method. The data obtained comes from field studies, literature studies, scientific journals, research results, credible websites, or other publications. The results show that the spatial arrangement of Fatahillah Museum symbolizes the timeline of Jakarta's history so that visitors can walk through it like time travelers. However, other architectural elements on the facade or other decorations do not convey a specific message or philosophy as to why they are implemented in Fatahillah Museum